Reducing the pollutant load of olive mill wastewater by photocatalytic membranes and monitoring the process using both tyrosinase biosensor and COD test - Martini, Elisabetta; Tomassetti, Mauro; Campanella, Luigi; Fortuna, Antonio (Frontiers in Chemistry, 2013)
Photocatalytic technique had already been employed in the treatment of olive mill wastewater (OMW) using the photocatalysis in suspension. The coupling of photocatalytic and membrane techniques should result in a very powerful process bringing great innovation to OMW depollution. Despite the potential advantages using these hybrid photoreactors, research on the combined use of photocatalysis and membranes has so far not been sufficiently developed. The present paper describes a study to assess the photocatalytic efficacy of a new ceramic membrane containing titanium dioxide, irradiated by UV light, used to abate the pollutant load of olive mill wastewater. Good results were obtained (more than 90% of the phenol content was removed and the COD decrease was of the order of 46-51 % in 24 h) particularly using the ceramic membrane compared with those offered by analogous catalytic membranes made of metallic or polymeric materials.